2004
DOI: 10.1111/j.1524-4725.2004.30430.x
|View full text |Cite
|
Sign up to set email alerts
|

Microfoam Ultrasound-Guided Sclerotherapy Treatment for Varicose Veins in a Subgroup with Diameters at the Junction of 10 mm or Greater Compared with a Subgroup of Less Than 10 mm

Abstract: Ultrasound-guided foam sclerotherapy is effective in treating all sizes of varicose veins with high patient satisfaction and improvement in quality of life. Duplex ultrasound findings demonstrated a small increase in failure to close the saphenofemoral or saphenopopliteal junction with increasing size of junction diameter, but this does not significantly alter the results with respect to clearance of visible varicosities and patient satisfaction with results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 20 publications
1
42
1
Order By: Relevance
“…The other studies looking at HRQOL after USGFS are limited because of short follow-up, by the use of only a disease-specific instrument, 28 by looking at a combination of surgery and USGFS, 11 or by simply asking patients whether their QOL had improved. 29 Our previous studies have shown that recurrent VVs are more symptomatic at baseline than primary veins and that the improvement in HRQOL (measured by AVSS) after surgery for recurrent VVs is less than that achieved for primary disease. 16 The results from the current study after USGFS were very similar.…”
Section: Discussionmentioning
confidence: 98%
“…The other studies looking at HRQOL after USGFS are limited because of short follow-up, by the use of only a disease-specific instrument, 28 by looking at a combination of surgery and USGFS, 11 or by simply asking patients whether their QOL had improved. 29 Our previous studies have shown that recurrent VVs are more symptomatic at baseline than primary veins and that the improvement in HRQOL (measured by AVSS) after surgery for recurrent VVs is less than that achieved for primary disease. 16 The results from the current study after USGFS were very similar.…”
Section: Discussionmentioning
confidence: 98%
“…Feasibility, effectiveness, efficacy 4,6,[17][18][19]21,[23][24][25][26][27][28][29]31,34,[37][38][39] and comparative 5,7,10,[12][13][14][15][16]20,22,[40][41] studies have been conducted in many countries and distinct continents. The transition from air to a physiologic gas has been supported by the experience of Cabrera in Spain and by the international trials conducted by Provensis to test the physiologic mix Varisolve.…”
Section: Discussionmentioning
confidence: 99%
“…4,6,7,[9][10][11][12][13][14][15][16] Patients of all abnormal, clinical, CEAP classes have been treated with UGFS. 1,2,4,6,7,[11][12][13][14][16][17][18][19][20][21][22][23][24][25][26][27][28] Foam sclerotherapy has been used to successfully treat: (1) saphenous veins primarily, (2) to complement, complete, or extend stripping or thermal ablation by laser or radiofrequency, (3) recurrent veins, (4) venous malformations, (5) venous aneurysms, (6) sciatic nerve varices, and (7) saphenous or nonsaphenous perforating veins. Side effects and adverse events have been described not only for UGFS but for all methods of treating the superficial veins of the lower extremity, surgical or nonsurgical.…”
mentioning
confidence: 99%
“…Varicosities with small and large diameters can be treated with UGFS but saphenous veins with J AM ACAD DERMATOL VOLUME 60, NUMBER 1 diameters of 10 mm or more may require multiple treatments and large volumes of foam (up to 3 sessions and 15 cc of foam). 17 UGFS can be used in patients with severe chronic venous insufficiency (CVI) and may enhance ulcer healing. 18 This technique is also used to treat perforator veins and congenital venous malformations (Table I).…”
Section: Indicationsmentioning
confidence: 99%